Reductionism and holism in the light of recentivism - Baron, Adam (Folia Philosophica, 2003)
It is commonly known that reductionism and holism are mutually opposed stances, which represent opposite ends of the spectrum. The question arises how those opposite notions can be related to the principles of recentivism. The author consciously used those polar ideas to demonstrate that the whole conception of recentivism appears to be a reductionist current of thought. Ultimately, the author of the article wanted to show that globalising (holistic) theories do not describe reality so precisely as reductionist conceptions of which the philosophy of recentivism is one. It has to be conceded that reductionism is the dominant stance. The author juxtaposed it on purpose with holism in order to foreground the features of reductionism itself. It is holism that is closet to various programmes of the unification of power.